INVITRO ANTIOXIDANT AND HEMIN BIOMINERALIZATION INHIBITORY PROPERTIES OF Cassia sieberiana DC. AQUEOUS STEM BARK EXTRACT (FUDMA JOURNAL OF SCIENCES, 2023)
Medicinal plants are the most affordable source of disease treatment in Africa. Different parts of plants are screened for their curative and disease management of various illnesses. Cassia sieberiana (D.C) is a medicinal plant widely distributed in the Southern Sahel, Sudan Savanna and distributed in the semi-arid north eastern part of Nigeria. It is a source of some bioactive compounds and has an antioxidant activity. This study was aimed to determine in-vitro antioxidant and hemin biomineralization inhibitory properties of Cassia sieberiana (D.C). Aqueous stem bark extract. Phytochemicals screening and in vitro free radical scavenging activity of aqueous stem bark extract of Cassia sieberiana D. C was conducted using 3 – 5 weeks old albino rats .Results showed the presence of carbohydrates, alkaloids, tannins, flavonoids, saponins and steroids. The extract displayed significant scavenging activity of DPPH at higher concentration doses (9mg/ml). The extract displayed non-hemolytic activity at high concentrations, with the maximum inhibition at 8mg/ml, while the inhibition of hemolysis induced by PHZ (phenylhydrazine) was dose dependent, with a significant increase in erythrocyte membrane protection at 10mg/ml, with IC50 at 1.729 mg/ml. The extract displayed potential antimalarial activity against the bio-mineralization of heme, increased inhibition was exhibited with increased concentration (IC50 =5.808). These findings suggest that the aqueous extract of Cassia sieberiana possesses antimalarial properties likely mediated due to the presence of secondary metabolites and its ability to scavenge free radicals prevents the bio-mineralization of heme. Thus, it can be further explored for the effective management of malaria.
Keywords: Cassia sieberiana, DPPH, Phytochemical, Hemolysis